(3TQM GdYbGFO GdfSajIs - (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s ((3Ydi Hf CMeO s)
(3ChdgG (B:s
(3GdMeO ddg GdeJhMO HLdGd PGJg hceGd UaGJg hHYO aEf eHfi Yde GdTQGFY hGdCMcGe , hCSGS bhGYO YbGFO GdESdGe , gh Yde GdJhMjO hGdUaGJ s
(3BNQgG (B:s
(3aGdJQbi hGdYdh EfeG gh ai GdCUd GdJLQO hEXgGQ GdBKGQ GdKhjI , dGai eWdb GdTQa hGdceGd ddOdGdI Ydi CaVdjI GdedGFcI HgPG , hGddg CYde HMbjbI GdMGd hhKjbI GdebGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B219 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B228 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B430s
Keywords: (3GdJhMjO hGdedd hGdfMds